Clinicopathological characteristics and treatment patterns of combined small-cell lung cancer: a real-world single-center study with a mini review - Gong, Liu; Li, Hongsen; Shou, Jiawei; Sheng, Jin; Jin, Wei; Lou, Haizhou; Li, Da; Hu, Hong; Fang, Yong (Frontiers in Immunology, 2025)
BackgroundCombined small-cell lung cancer is a rare subtype of SCLC, which is characterized by the coexistence of SCLC with any histological type of non-small cell lung cancer. There is limited clinical data. We aimed to explore the clinicopathological features and prognosis of C-SCLC patients who received anti-tumor therapy.MethodsEligible patients were histopathologically confirmed adult C-SCLC who received anti-tumor treatment at Sir Run Run Hospital. This analysis aimed to describe the clinicopathological characteristics and evaluate the tumor response rate (RR), disease control rate (DCR), and progression-free survival (PFS).ResultsThirty patients were included. Eighty-three point three three percent were male, and sixty-six point six seven percent were non-smokers. Squamous cell carcinoma (SCC; 11/30) and adenocarcinoma (AC; 11/30) were the most frequently observed mixed components, followed by large-cell neuroendocrine carcinoma (LCNEC; 8/30). Patients received immunochemotherapy (13/30), platinum-based chemotherapy (9/30), or anti-EGFR-/anti-VEGF-based therapy (8/30). Most patients used the anti-PD-1 inhibitor Serplulimab (n=7). Among 27 patients with measurable disease, the RR and DCR were 51.85% (95% CI: 31.95 - 71.33%) and 85.19% (95% CI: 66.27 - 95.81%), respectively. The median PFS was 9.70 months (95% CI: 4.37 - 18.73). The median PFS of C-SCLC mixed with LCNEC was higher than that of those mixed with AC or SCC (10.62 vs. 9.70 vs. 4.17 months; P = 0.858); patients are more likely to benefit from immunotherapy than from chemotherapy and targeted therapy (9.70 vs. 5.27 vs. NR months; P = 0.685).ConclusionOur findings provide a basis for systematic treatment strategies in C-SCLC and suggest that patients may derive benefit from immunotherapy, although further studies are needed to confirm these observations.